Analysis of the Concepts of the Objective Aspect of Homicide and Culpable Bodily Harm - Erik Ploth; Stanislav Mihálik (Societas et Iurisprudentia, 2024)
In the paper, the authors focus on the analysis of the objective aspect of the crime of homicide and culpable bodily harm with an emphasis on the caused consequence. In addition to the traditional approaches to the interpretation of relevant concepts, they focus their attention on interpretative problems occurring in application practice, while also pointing out possible ways of solving them. Finally, special attention is paid to the process of imputation of special qualifying terms (circumstances conditioning the application of a higher penalty rate), the authors point out the need to avoid application duality in the process of imputation of these features, i.e. to proceed in accordance with the substantive line of the ne bis in idem principle.